(untitled) (Global Journal of Science Frontier Research, 2017)
Three (3) indigenous bacteria species (Bacillus spp, Acinectobacterspp and Moraxella spp) previously isolated from contaminated soil of some auto mechanic workshops were used for bioremediation studies on some irrigation water used at Sarkin-nomaFadama farms located in LokojaKogi State, Nigeria. This was done in order to investigate their bioremediation potentials using a simple pour plate method. The physicochemical parameters and heavy metal analysis (using AAS iCE 3000) of the irrigation water were performed before and after inoculation of the isolated organisms. Nitrate and phosphate concentration were found to be 10.56mg/L and 12.63mg/L prior to inoculation while iron and zinc were 0.9569mg/L and 0.2245mg/L respectively.